Contingency-based emotional resilience: effort-based reward training and flexible coping lead to adaptive responses to uncertainty in male rats - Lambert, Kelly G.; Hyer, Molly M.; Rzucidlo, Amanda A.; Bergeron, Timothy; Landis, Timothy; Bardi, Massimo (Frontiers in Behavioral Neuroscience, 2014)
Emotional resilience enhances an animal’s ability to maintain physiological allostasis and adaptive responses in the midst of challenges ranging from cognitive uncertainty to chronic stress. In the current study, neurobiological factors related to strategic responses to uncertainty produced by prediction errors were investigated by initially profiling male rats as passive, active or flexible copers (n=12 each group) and assigning to either a contingency-trained or non-contingency trained group. Animals were subsequently trained in a spatial learning task so that problem solving strategies in the final probe task, as well various biomarkers of brain activation and plasticity in brain areas associated with cognition and emotional regulation, could be assessed. Additionally, fecal samples were collected to further determine markers of stress responsivity and emotional resilience. Results indicated that contingency-trained rats exhibited more adaptive responses in the probe trial (e.g., fewer interrupted grooming sequences and more targeted search strategies) than the noncontingent-trained rats; additionally, increased DHEA/CORT ratios were observed in the contingent-trained animals. Diminished activation of the habenula (i.e., fos-immunoreactivity) was correlated with resilience factors such as increased levels of DHEA metabolites during cognitive training. Of the three coping profiles, flexible copers exhibited enhanced neuroplasticity (i.e., increased dentate gyrus doublecortin-immunoreactivity) compared to the more consistently responding active and passive copers. Thus, in the current study, contingency training via effort-based reward training, enhanced by a flexible coping style, provided neurobiological resilience and adaptive responses to prediction errors in the final probe trial. These findings have implications for psychiatric illnesses that are influenced by altered stress responses and decision-making abilities (e.g., depression).